Fish as a source of (micro)nutrients to combat hidden hunger in Zambia - Nils Nölle; Sven Genschick; Klaus Schwadorf; Holger Hrenn; Sonja Brandner; Hans Konrad Biesalski (Food Security, 2020)
Fish is an excellent source of protein, but can also be a good source of micronutrients. In Zambia fish is the main animal food source for poor women and children, two groups which are likely to suffer from inadequate micronutrient supply (hidden hunger). Although the potential of fish to combat hidden hunger is increasingly recognized and fisheries and aquaculture have been identified as key resources in addressing food and nutrition security issues in Zambia, only limited information on the nutrient composition of consumed fish species and products is available. Thus the objectives of this paper are to give a quantitative description of the nutritional composition of fish and fish products consumed in Zambia, and to estimate their potential to the Recommended Daily Intakes (RDIs) of micronutrients. Therefore approximately forty fish species in various kinds of processing were collected and prepared following local customs. Samples were analysed for macronutrients such as protein and fat. Contents of B-vitamins and minerals were also analysed. Protein content was overall similar, while fat content and fatty acid composition varied considerably. Most fish contained high amounts of niacin and cobalamin, but small fish usually contained the most cobalamin. Small fish contained up to 32 times the amount of calcium than other fish and often contained more iron and zinc, too. Overall small fish species, which are commonly consumed by poor women and children, can be used to combat hidden hunger in Zambia, due to high levels of cobalamin, calcium, iron and zinc.
Keywords: 630; Hidden hunger; Malnutrition; Micronutrients; Zambia; Fish; Fish products